PENGARUH KEBIJAKAN DIVIDENT (DIVIDENT POLICY), RASIO LANCAR (CURRENT RATIO), DAN MARGIN LABA BERSIH (NET PROFIT MARGIN)TERHADAP COMPANY VALUE PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA - Purnasari, Nina; Lilia, Wirda; Haloho, Ascriyani; Tampubolon, Ribka Uli (EDUTECH CONSULTANT, 2019)
This study aims to examine the effect of dividend policy, current ratio, and net profit margin on companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in the 2012-2016 period. There is a phenomenon of increasing dividend policy, current ratio, and net profit margin in the Consumer Goods Industry Sector Companies listed on the Indonesia Stock Exchange in the 2012-2016 period. The approach used in this study is a Quantitative Approach, the type of research used is quantitative descriptive. and the nature of research is causal. This research method uses a purposive sampling method, with a sample of 16 companies. The method of data collection uses documentation, the type of data in the form of quantitative data, and data sources in the form of secondary data. The data analysis method used is multiple linear regression. the coefficient of determination in this study is 53%, which means that 53% of the company value can be explained by divident policy, current ratio, and net profit margin. The results of the study show that dividend policy has partially a significant positive effect on company value. Current ratio (current ratio) partially has a negative effect and net profit margin (partial net profit margin) has a positive and not significant effect on company value.